Versatile and Highly Efficient Controls of Reversible Topotactic Metal–Insulator Transitions through Proton Intercalation. (7th October 2019) - Chen, Shanquan; Zhou, Haiping; Ye, Xing; Chen, Zuhuang; Zhao, Jinzhu; Das, Sujit; Klewe, Christoph; Zhang, Lei; Lupi, Eduardo; Shafer, Padraic; Arenholz, Elke; Jin, Dun; et al.
Abstract: The ability to tailor a new crystalline structure and associated functionalities with a variety of stimuli is one of the key issues in material design. Developing synthetic routes to functional materials with partially absorbed nonmetallic elements (i.e., hydrogen and nitrogen) can open up more possibilities for preparing novel families of electronically active oxide compounds. Fast and reversible uptake and release of hydrogen in epitaxial ABO3 manganite films through an adapted low‐frequency inductively coupled plasma technology is introduced. Compared with traditional dopants of metallic cations, the plasma‐assisted hydrogen implantations not only produce reversibly structural transformations from pristine perovskite (PV) phase to a newly found protonation‐driven brownmillerite one but also regulate remarkably different electronic properties driving the material from a ferromagnetic metal to a weakly ferromagnetic insulator for a range of manganite (La1− x Sr x MnO3 ) thin films. Moreover, a reversible perovskite‐brownmillerite‐perovskite transition is achieved at a relatively low temperature ( T ≤ 350 °C), enabling multifunctional modulations for integrated electronic systems. The fast, low‐temperature control of structural and electronic properties by the facile hydrogenation/dehydrogenation treatment substantially widens the space for exploring new possibilities of novel properties in proton‐based multifunctional materials. Abstract : Perovskite oxides are of prime importance to multifunctional materials. Hydrogen is efficiently incorporated into epitaxial perovskite manganite films, which permits reversible perovskite‐brownmillerite‐perovskite transitions, accompanied by notable modulations from a ferromagnetic, metallic perovskite phase to a weakly ferromagnetic, insulating hydrogenated‐brownmillerite phase. This facile hydrogenation substantially widens the space for novel properties in proton‐based multifunctional materials.